Investigating the Influence of Work-Life Balance Strategies on Work Behaviour among Employees of selected Broadcasting Firm, Ibadan, Nigeria - Akinbo, Tina Martha; Ayodele, Alafiatayo (NIU Journal of Humanities, 2022)
Balancing a successful career with personal and family life can be challenging as it has impact on work behaviour and personal life’s roles. Many employees often experienced difficulties in attempting to balance employment responsibilities with their social life due to the shortfall of positive strategies emplaced in organisations. This study attempts to investigate the work life balance strategies and its influence on employee behaviour among employees in radio Nigeria. Study adopted a descriptive survey research design with social exchange theory giving a conceptual guide to the study. T aro Yamane’ s formula for sample size determination was engaged to select 200 participants from the population of 500 as stratified random sampling technique was further deployed. The study is a mixed method as semi-structured instrument and in-depth interview guide was used in gathering both quantitative and qualitative data. The findings of this study revealed that work life balance had a significant influence on job involvement of employees (r = .386**, N= 200, P < .05). It was concluded that there is a significant relationship between work life balance and job involvement. Therefore study further established the significant influence between work life balance and job engagement among employees in the selected study organisation. The study however recommended that organization should ensure they formulate, modify and implement work life balance model as a corporate culture to drive higher employee performance and engagement. Hence to achieve competitive advantage, work life balance must be a continuum and constantly evaluated for possible modification. Keywords: Work-Life Balance, Work Behaviour, Job Engagement, Human Resource Management, Job Involvement